A rare case of NIPT discrepancy caused by the placental mosaicism of three different karyotypes, 47, XXX, 47, XX, +21, and 48, XXX, +21. Issue 8 (28th May 2020) - Li, Jin; Xie, Mingshui; Wang, Fang; Ma, Jianhong; Li, Jiafu; Chen, Chen; Li, Zhimin; Wang, Juan; Zhang, Yuanzhen; Li, Yirong
Abstract: Background: Placental mosaicism is one of the major reasons for noninvasive prenatal testing (NIPT) discrepancy. Herein, we discovered a rare case of placenta with complex karyotypes that caused false‐positive and false‐negative results in noninvasive prenatal testing. Methods: Next‐generation sequencing (NGS) and Quantitative fluorescent polymerase chain reaction (QF‐PCR) were performed on the cord blood sample, fetal tissues, and eight placental biopsies. Fluorescent In Situ Hybridization (FISH) and karyotyping were also carried to confirm the fetal genome status. Results: The results suggested that the fetal chromosome was 47, XXX and the placenta had three karyotypes of 48, XXX, +21, 47, XX, +21, and 47, XXX. QF‐PCR indicated that the extra chromosome 21 and chromosome X were all from the father. It is speculated that the zygote may have 48, XXX, +21 karyotype and trisomy rescue could be the main mechanism for the development of the homogeneous fetus and complex mosaic placenta. Conclusion: Overall, the complicated nature of our case underlines the importance of discussing with parents the possibility of both atypical and discordant results during preconfirmatory amniocentesis counseling and consent. Abstract : The composition of the unusual placental mosaicsim that caused NIPT discrepancy was complex. The karyotype for the paternal sperm may be an unusual diploid gamete (25, XX, +21) and zygote is likely to be a double trisomy (48, XXX, +21). After the fifth cleavage, the zygote grows into a morula and then into a blastocyst. The blastocyst contains two major part of compositions. One is the inner cell mass (yellow), which develops into the embryo (the homogeneous 47, XXX). The other is trophoblast cells (blue), which develops with some inner cell mass into the placenta (the mosaic 47, XXX, 47, XX, +21 or 48, XXX, +21).